Experimental investigation of various copper oxide electrodeposition conditions on photoelectrochemical hydrogen production. (9th March 2017) - Bicer, Yusuf; Chehade, Ghassan; Dincer, Ibrahim
Abstract: In this study, an experimental investigation of photosensitive material copper oxide electrodeposition on various substances is performed under different experimental conditions in order to evaluate the effects on photoelectrochemical hydrogen production system. The experimental setup consists of solar simulator, electrodeposition chemicals, hydrogen sensor, pH meter, graphite and platinum electrodes, heating plate, stirrer, temperature sensors, cathode and anode plates, concentrating lens and potentiostat. The overall aim is to optimize the efficiencies by generating higher currents and eventually hydrogen as light enhances the separation of water process. The results obtained in this study are promising for photoelectrochemical hydrogen production under the solar simulator and concentrated light irradiation conditions. Furthermore, an electrolysis setup using the coated metals and graphite rod is built to investigate the amount of photocurrent production. The characterization is also conducted under light and no-light conditions, where the amount of produced current and hydrogen increased in light compared to no-light condition. At the applied voltage of −0.6 V and −0.4 V vs. Ag/AgCl, the photocurrent densities of 0.8 mA/cm 2 and 0.27 mA/cm 2 are obtained with a solar conversion efficiency of 0.86% and 0.24%, respectively. Highlights: Copper oxide is deposited on metal substrates under various conditions. Photocurrent production is examined using solar simulator and concentrated light. Concentrated light conditions yield higher photocurrent values. Deposition of copper oxide enhances the photoelectrochemical hydrogen production.